Editorial of dossier “Wrongful convictions and prosecutions: current status, causes, correction and reparation mechanisms” - Mauricio Duce; Keith A. Findley (Revista Brasileira de Direito Processual Penal, 2022)
This paper provides an overview of several central topics for comparative research on wrongful convictions and prosecutions (near misses). The work addresses three issues: studies that attempt to establish the quantity or frequency of errors; research that investigates the factors that increase the likelihood of their occurrence; and, finally, research on the mechanisms for correcting and compensating them. In each area, advances in available knowledge are identified, but also that we are still far from having all the information that would be required. We aim to serve as an introduction to this special issue of the RBDPP and as a starting point for those who wish to know state of the art on the subject.